2021
DOI: 10.1007/s12325-021-01646-5
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and Safety of COPD Maintenance Therapy with Tiotropium/Olodaterol versus LABA/ICS in a US Claims Database

Abstract: Introduction In patients with chronic obstructive pulmonary disease (COPD), treatment with long-acting muscarinic antagonist (LAMA)/long-acting β 2 -agonist (LABA) combination therapy significantly improves lung function versus LABA/inhaled corticosteroid (ICS). To investigate whether LAMA/LABA could provide better clinical outcomes than LABA/ICS, this non-interventional database study assessed the risk of COPD exacerbations, pneumonia, and escalation to triple therapy i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 47 publications
1
6
0
Order By: Relevance
“…Cumulative literature pointed out that LABA/LAMA FDC may be more efficacious while having less adverse reactions such as lower respiratory tract infections than LABA/ICS FDC. [21][22][23][24] Our results, to some extent, reflect that FDC prescription patterns in daily practice may adhere to the recommendations of available evidence.…”
Section: Comparison With Existing Studiessupporting
confidence: 64%
See 1 more Smart Citation
“…Cumulative literature pointed out that LABA/LAMA FDC may be more efficacious while having less adverse reactions such as lower respiratory tract infections than LABA/ICS FDC. [21][22][23][24] Our results, to some extent, reflect that FDC prescription patterns in daily practice may adhere to the recommendations of available evidence.…”
Section: Comparison With Existing Studiessupporting
confidence: 64%
“…Patient Characteristics for LABA/LAMA FDC or LABA/ICS FDC Use Some comparative effectiveness or safety studies of LABA/LAMA and LABA/ICS combination therapies (either FDC or free combination forms) noticed that baseline patient characteristics differed between treatment groups. 23,24,28,29 For example, in one study using a US commercial claims database, Samp et al showed that patients who started LABA/ LAMA combination therapy were older, more likely to be male, had more comorbidities, including cardiovascular diseases, any cancer, lung cancer, mental health disorder, and pneumonia, and had more frequent resource utilization due to COPD compared to patients who started LABA/ICS combination therapy. 29 Similar to Samp et al's results, our study also found that LABA/LAMA FDC initiators were generally more vulnerable than LABA/ICS FDC initiators.…”
mentioning
confidence: 99%
“…This may have biased findings, since patients prescribed multiple inhalers are more likely to be nonadherent to treatment and require urgent care visits, emergency department visits, and hospitalizations compared with patients receiving the same therapy via combination inhalers . A third study, which found a benefit for LAMA-LABA therapy via a single inhaler, analyzed only 1 LAMA-LABA (tiotropium-olodaterol) and included patients using other LAMA-LABAs during the washout period while excluding those who used ICS-LABAs, which may have biased findings toward tiotropium-olodaterol. All 3 studies were limited by small sample sizes in the exposure group.…”
Section: Discussionmentioning
confidence: 99%
“…A Japanese real‐world study suggested that, compared with new users of tiotropium, new users of tiotropium/olodaterol had a numerically lower probability of escalating to triple therapy or experiencing moderate or severe COPD exacerbations 94 . Furthermore, data from the US HealthCore Integrated Research Database revealed that both individually and in combination, tiotropium/olodaterol was associated with a lower risk of COPD exacerbations, pneumonia and escalation to triple therapy in patients with COPD compared to ICS/LABA 95 ; the combined risk was reduced regardless of baseline eosinophils or exacerbation history.…”
Section: Efficacy Of Dual Bronchodilation In the Real Worldmentioning
confidence: 99%
“…Furthermore, data from the US HealthCore Integrated Research Database revealed that both individually and in combination, tiotropium/olodaterol was associated with a lower risk of COPD exacerbations, pneumonia and escalation to triple therapy in patients with COPD compared to ICS/LABA95 ; the combined risk was reduced regardless of baseline eosinophils or exacerbation history.8 | A NEW PARADIGM IN COPD THERAPY: USING DUAL BRONCHODILATION AS INITIAL MAINTENANCE TREATMENTOptimising bronchodilation requires concurrent modification (blockade on one side and stimulation on the other) of both the parasympathetic and sympathetic arms of the autonomic nervous system 12. …”
mentioning
confidence: 99%